Access to pre-hospital care among patients visiting emergency department of a tertiary hospital in Nepal: A Mixed Methods pilot study - Bhattarai, Noney; Thapa Pachya, Ambika; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Introduction: Pre-hospital care covers assistance and immediate care to injured and seriously ill patients at the scene and during transfer to health facilities. Pre-hospital care demands skills and preparedness. Medical emergencies involve use of a range of transports other than ambulances in Nepal. The current pilot study aimed to explore the access to pre-hospital care and factors associated with it from both users and providers’ perspective.Method: Cross sectional concurrent parallel mixed method study was done in emergency department (ED) of Patan Hospital, Nepal. Semi-structured questionnaire and interview guides were used. Thirty patients and visitors arriving at ED and seven key informants participated. Permission was taken from ED and written informed consent was taken. Descriptive and inferential statistics was done using R software and thematic analysis was done using EZR package.Result: Proportion of access to pre-hospital (PH) care was found to be 13.3% (4 out of 30). Concept of prehospital care itself is not popular among users. Limited PH care and service was found in the study site. Cost of transportation and distance between site and hospital were found to be associated with access. Further to it, barriers and facilitators were related with service delivery, workforce, financing, infrastructure, communication, coordination and information.Conclusion: Access to pre-hospital services was found only in 4 out 30 patients. Awareness among the users and integrated governance of ambulances is recommended for improvement of pre-hospital services.